2016
DOI: 10.1007/978-3-319-28782-9_8
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Applications of Carbon Dots

Abstract: Carbon materials have been used for a long time in heterogeneous catalysis, which can satisfy most of the desirable properties required for a suitable catalyst support. Based on their significant advantages, such as low cost, huge amount, easy accessibility, high surface area, diverse porous structure, and resistance to acidic or basic environments, the carbon nanostructures are hungered for using as proper catalysts directly. Carbon dots (CDs), a new class of carbon nanomaterials with sizes below 10 nm, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 225 publications
1
7
0
Order By: Relevance
“…Inspired by these findings, we recently found that the CD size also played an important role in photocatalysis. For example, CDs with size smaller than 5 nm could play well with near-infrared light illumination, resulting in 100% selective oxidation of benzyl alcohol to benzaldehyde . For CDs with size larger than 5 nm, a tremendous amount of photogenerated protons could be produced in aqueous solution under visible light illumination, enabling exceptional photocontrolled acid catalytic ability for many reactions such as esterification and Beckmann rearrangement .…”
Section: Strategies To Tailor Cds For Specific Applicationsmentioning
confidence: 99%
“…Inspired by these findings, we recently found that the CD size also played an important role in photocatalysis. For example, CDs with size smaller than 5 nm could play well with near-infrared light illumination, resulting in 100% selective oxidation of benzyl alcohol to benzaldehyde . For CDs with size larger than 5 nm, a tremendous amount of photogenerated protons could be produced in aqueous solution under visible light illumination, enabling exceptional photocontrolled acid catalytic ability for many reactions such as esterification and Beckmann rearrangement .…”
Section: Strategies To Tailor Cds For Specific Applicationsmentioning
confidence: 99%
“…Carbon dots (CDs) with sizes below 10 nm are found to be efficient catalysts or photocatalysts [ 154 ]. The versatility of surface modification towards different CQD groups enables them to absorb lights of various wavelengths, thus providing good prospects for photocatalytic applications.…”
Section: Emerging Applications Of Carbon Dotsmentioning
confidence: 99%
“…Carbon dots (CDs), with sizes below 10 nm found efficient catalyst or photocatalysts [154]. The versatility of surface modification towards different CQD groups enables them to absorb lights of various wavelengths that provides good prospects for photocatalytic applications.…”
Section: Catalysismentioning
confidence: 99%